Pengaruh Terpaan Berita Hoax dan Persepsi Masyarakat Tentang Kualitas Pemberitaan Televisi Berita Terhadap Intensitas Menonton Televisi Berita - Ghana Pratama, Albert; Pradekso, Tandiyo (Interaksi Online, 2018)
Spread of hoaxes that occurs during 2016 -2018 impacted many aspects and caused the media literacy of people to filter the information they received to be very low. Simultaneously, quality index of news television released by KPI scored television news quality are still on the below of minimum criteria. Therefore, the purpose of this research is to understand the relevancy of hoax and people’s perception on television news program towards the intensity of the people to watch television news. This research is a quantitative-explanatory research. By using non-probability sampling with amount of 50 samples between 17-60 years old Indonesian who exposed hoax news and watched television news. The result of multiple regression analysis shows that there is no influence between the exposure of hoax news and public perception towards the quality of television news coverage to the intensity of watching television news, shown by the significance value of 0.478> (α) = 0.05. With these results it is advisable to policy makers such as KPI and Media Owner and future researchers to not only focus on the eradication of hoax, but also to be able to increase the media literacy of the community and in addition, for media companies to conduct research and invest in alternative information dissemination to meet the needs of society that has not been met.